MENINGKATKAN HASIL BELAJAR MUATAN PPKn MATERI PERSATUAN DAN KESATUAN TERHADAP KEHIDUPAN BERBANGSA DAN BERNEGARA MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA SISWA KELAS VI SDN 91 KENDARI SEMESTER 1 TAHUN PELAJARAN 2022/2023 - Irmayani Irmayani (CV. ADIBA AISHA AMIRA, 2023)
The results of the previous test, namely the daily test test in class VI at SDN 91 Kendari, showed that student learning outcomes were not optimal, because there were still several students who did not meet the minimum completeness criteria. Of the 22 students, there were around 7 students whose learning outcomes were still low. Learning strategies that will be used in existing problems are taken to make appropriate improvements through creative and fun methods, namely the use of project based learning learning models. This study uses an action research model (action research). An action that is specifically observed continuously, seen for pluses and minuses, then controlled changes are made to the maximum effort in the most appropriate form of action. This is in accordance with what is done by researchers. The subject of this research was Class VI of SDN 91 Kendari, which consisted of 22 students. The results of the pre-cycle research obtained classical student learning outcomes of 31.81% in the